Cytogenetic stability and genome size variations in newly developed derived Brassica juncea allopolyploid lines - Mehak Gupta; Chhaya Atri; SS Banga (Journal of Oilseed Brassica, 2026)
Allopolyploids are normally resynthesized through interspecific hybridization and whole genomeduplication. Brassica group has developed a new concept of derived digenomics, where anallopolyploid Brassica is synthesized through hybridization of two nonparental digenomic species. Geneticdifferences in allopolyploids result from recombination between the hybridized subgenomes or structuralvariation in cohabiting genomes which can significantly impact genetic constellations and consequently thephenotype. We analysed 62 Brassica juncea progenies, developed following hybridization between B. napusand B. carinata, for cytogenetic stability and genome size changes in S5 and S6 generations. In derivedB. juncea genotypes, pollen grain stainability ranged from 65 to 95 percent. Meiotic analysis of the derivedB. juncea lines conducted during S5 and S6 generations revealed standard 18II configuration for the majorityof test genotypes. During S5 generation, some genotypes revealed abnormal meiotic configurations. Thesegenotypes were: DJ 1-1, DJ 22, DJ 25, DJ 115, DJ 116 (all 18II+1I), DJ 21 and DJ 19-2 (both 19II) and DJ55 (17II). All these genotypes generally had monosomic or disomic addition of, possibly, one chromosomeeach from C genome. Anaphase I distribution was also aberrant in these genotypes. This perhaps causedimpaired pollen fertility. One generation of selfing and selection for improved fertility, however, led to correctionof meiotic aberrations in all these instances. All the derived B. juncea genotypes were crossed as femalewith natural B. juncea to identify random chromosome substitutions. All the consequent F1 genotypes werecytologically analysed during meiosis1. Occurrence of 17II and 2I in the F1with natural euploid B. juncea wasconsidered to be indicative of substitution for one chromosome pair. Disomic chromosome substitution wasindicated for DJ 15, DJ 18, DJ 19-2, DJ 21, DJ 38, DJ 58, DJ 61, DJ 92, DJ 97, DJ 103 and DJ113. Molecularcharacterization helped to resolve these substitution lines into six distinct groups. Most of these substitutionlines are expected to involve A/ C substitutions. Genome size variations were also observed. On the basis ofpopulation mean (over 62 derived juncea types), average genome size was 528.274 Mbp, representing adecline of almost 1.072 percent DNA during six generations of selfing following allopolyploidization. Thesestudies confirmed the viability of the concept of developing derived amphiploids.